Pengaruh Citra Merek, Promosi Dan Kepercayaan Merek Terhadap Keputusan Pembelian Pada Produk Scarlett Whitening (Studi Kasus Mahasiswi Uin Raden Intan Lampung) - Agilia Syafitri; Eca Ratna Sari; Vicky F Sanjaya (Universitas Muhammadiyah Sumatera Utara, 2021)
This study aims to analyze the effect of brand image, promotion, and brand trust on purchasing decisions on Scarlett Whitening products. This study used 50 respondents. The analytical method used is multiple linear regression with a significant level (?) of 0.05. The results of this study indicate that product brand image has a positive and significant effect on consumer purchasing decisions, with a positive value of 0.228 and a significant value of 0.030 less than 0.05. Promotion variable has a negative and insignificant effect on consumer purchasing decisions, with a negative value of -0.148 and an insignificant 0.276 more than 0.05. And the variable brand trust has a positive effect of 0.797 and a significant 0.000 affects purchasing decisions.Keywords : Brand Image, Promotin, Brand Trust, Purchasing Decision